2016
DOI: 10.1017/s0033291716002816
|View full text |Cite
|
Sign up to set email alerts
|

Brain substrates underlying auditory speech priming in healthy listeners and listeners with schizophrenia

Abstract: The left STG/pMTG and their ASP-related functional connectivity with both the left caudate and some frontal regions (the left TriIFG in healthy listeners and the left Rolandic operculum in listeners with schizophrenia) are involved in the unmasking effect of ASP, possibly through facilitating the following processes: masker-signal inhibition, target-speech encoding, and speech production. The schizophrenia-related reduction of functional connectivity between the left STG and left TriIFG augments the vulnerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 92 publications
2
22
0
Order By: Relevance
“…Moreover, many studies have found that the connectivity in the INS decreased, which may cause the disrupted functional integration of the brain [30]. The ROL is mainly involved in language, and Wu et al suggested that the reduction of connectivity of ROL improves the vulnerability of speech recognition to speech masking [62]. Not only that, the work also showed that the ROL is bound up with hallucination [63].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have found that the connectivity in the INS decreased, which may cause the disrupted functional integration of the brain [30]. The ROL is mainly involved in language, and Wu et al suggested that the reduction of connectivity of ROL improves the vulnerability of speech recognition to speech masking [62]. Not only that, the work also showed that the ROL is bound up with hallucination [63].…”
Section: Discussionmentioning
confidence: 99%
“…Successful speech recognition under a speech-on-speech-masking condition involves multiple perceptual/cognitive processes, including target-speech detection, selective attention, sensory/working memory, and speech production. It is not surprising that speech recognition involves multiple brain regions with various perceptual/cognitive functions [ 5 10 ]. Although the augmented vulnerability to speech masking in people with schizophrenia may be associated with deficits of various perceptual/cognitive processes [ 5 7 , 11 14 ], it is the most important of all to know whether deficits in speech detection (the early-stage process) are the primary cause leading to deficits of speech recognition against informational speech masking.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that speech recognition involves multiple brain regions with various perceptual/cognitive functions [ 5 10 ]. Although the augmented vulnerability to speech masking in people with schizophrenia may be associated with deficits of various perceptual/cognitive processes [ 5 7 , 11 14 ], it is the most important of all to know whether deficits in speech detection (the early-stage process) are the primary cause leading to deficits of speech recognition against informational speech masking. We have recently reported that the performance in the task of target-speech detection, conducted by button-press, is poorer in people with schizophrenia than healthy listeners [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unmasking effect of VSP is normally based on the incorporation of several perceptual/cognitive processes, including the processing of speech information contained in lipreading, working memory of lipreading information, audiovisual integration during the co-presentation of the target speech and the masking speech, selective attention on target speech, and suppression of irrelevant masking signals (Wu et al, 2013a). People with schizophrenia, however, show impaired ability of using the temporally pre-presented lip-reading cue to improve target-speech identification against speech masking (Wu et al, 2013b), possibly suggesting a combined effect of working-memory deficits (Forbes et al, 2009), cross-modal-integration deficits (Ross et al, 2007; Wu et al, 2013b), and object-oriented-attention deficits (Zheng et al, 2016; Wu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%